Development of integrated village fund governance model with siberas public service application - Razak, Muhammad Rais Rahmat; B, Sofyan; Sofyan, Wahyudi; Lubis, Sandi; Rais, Tazkia Rhamdhiny (Edelweiss Applied Science and Technology, 2024)
This study introduces a comprehensive governance model designed to enhance the management of village funds in Indonesia. This model combines the Rais-MR3 system with the SIBERAS public service application. Village funds, established under Village Law No. 6 of 2014, are critical in advancing rural development. Nevertheless, challenges such as inefficiency, risks of corruption, lack of transparency, and limited public involvement have obstructed their effective management. This research aims to tackle these issues by creating a more robust governance framework that improves the efficiency and accountability of village fund management. Employing a qualitative approach, this research examines three case studies: the villages of Kalempang, Sipodeceng, and Bina Baru. Data collection methods included focus group discussions, in-depth interviews, and participatory observations, which provided detailed insights into the dynamics of village governance. The study's findings indicate that integrating digital governance tools, like the SIBERAS application, with the Rais-MR3 model substantially enhances administrative processes, boosts transparency and accountability, and diminishes corruption risks. Moreover, the model promotes increased public participation in decision-making, essential for achieving good governance. This research adds to the expanding body of literature on digital governance in rural environments by presenting a scalable governance model that other villages throughout Indonesia can adopt. The practical implications of the model suggest that its implementation may result in more effective service delivery, improved governance practices, and enhanced public trust—elements critical for sustainable rural development. Besides, the study emphasizes the importance of using technology to overcome governance challenges, providing a framework for other villages to improve transparency, accountability, and public engagement.